26th Annual Congress of the European College of Sport Science, 8th - 10th September 2021, Book of abstracts - Dela, F.; Helge, J. W.; Müller, E.; Tsolakidis, E. (26th Annual Congress of the European College of Sport Science, 8th - 10th September 2021, Book of abstracts, 2021)
Dear Valued Member of the ECSS Sport Science Community, Welcome to the 26th ECSS Annual Congress, 2021!